High-temperature-resistant polycarbonate-based composite material and preparation method thereof

By modifying silica powder and blending it with polycarbonate, high temperature resistant polycarbonate-based composite materials with high mechanical strength and heat resistance are prepared, which solves the problem that traditional polycarbonate materials cannot meet the aerospace and military industry resistance. Issues of thermal performance requirements.

CN119463443APending Publication Date: 2025-02-18ZHUZHOU DIBO PHOTOELECTRIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492179.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional polycarbonate materials cannot meet the high requirements for heat resistance in the aerospace and military industries.

Method used

After mixing the ammonia water, ethanol and deionized water, adding ethyl orthosilicate, silica powder is formed, and the modified powder is treated with 3-aminopropyltriethoxysilane and sulfonated polysulfone, and finally with Polycarbonate pellets are blended to prepare high-temperature resistant polycarbonate matrix composite materials.

Benefits of technology

It significantly improves the mechanical strength and heat resistance of polycarbonate-based materials, and meets the application requirements of high stress and high heat resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-temperature-resistant polycarbonate-based composite material. The preparation method comprises the following steps: (1) preparing silicon dioxide powder; (2) modifying an ethanol solution of 3-aminopropyltriethoxysilane and an N, N-dimethylformamide solution of sulfonated polysulfone to obtain primary modified powder; (3) mixing the primary modified powder with furan-2, 5-diketone and chlorobenzene, heating under the protection of nitrogen, adding sodium acetate and acetic anhydride, and heating to obtain doped powder; and (4) carrying out mixing, melt blending, extrusion granulation and injection molding on dried polycarbonate granules and the doped powder to obtain the high-temperature-resistant polycarbonate-based composite material. The polycarbonate-based composite material prepared by the method disclosed by the invention has relatively high mechanical strength and heat resistance, relatively high tensile strength and initial thermal degradation temperature, and can be used in occasions with relatively high requirements on material stress and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate materials, and in particular to a high-temperature resistant polycarbonate-based composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a general term for a class of thermoplastic polymers containing carbonate groups in the molecular structure. It is a class of engineering plastics with high light transmittance, good heat resistance and excellent mechanical properties. Its output is second only to polyamide among engineering plastics, and its application fields are wide. Although polycarbonate materials and their composite materials have extremely wide applications, with the development of the economy and the advancement of industrial technology, people continue to put forward higher and higher temperature resistance requirements for the application of polycarbonate materials. Such as automotive high-reflection headlight covers, spotlight housings, welding hole sleeves, hot steam sterilization safety valves, medical high-temperature sterilization vessels, etc., and in some special fields, such as: aerospace and military fields, the heat resistance of materials is required to be higher, and traditional polycarbonate cannot meet the use requirements. Therefore, high-temperature treatment of polycarbonate has become a research hotspot at home and abroad. Summary of the invention

[0003] To this end, the present invention provides a method for preparing a high temperature resistant polycarbonate-based composite material, the preparation steps comprising:

[0004] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, the mixed solution is heated to 60±5° C. in a water bath to keep the temperature, and then the mixed solution is stirred. Tetraethyl orthosilicate is added to the mixed solution under stirring. After the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for more than 3 hours to precipitate a solid phase, and then the solid-liquid separation is carried out, and the solid phase is dried to obtain silicon dioxide powder;

[0005] (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; soaking the silica powder in the ethanol solution of 3-aminopropyltriethoxysilane, stirring and mixing for more than 20 minutes, then adding deionized water to the solution under stirring, continuing to stir for more than 90 minutes after the addition is completed, then separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, drying, soaking the dried solid phase in the N,N-dimethylformamide solution of sulfonated polysulfone, stirring for more than 20 minutes, then separating the solid and the liquid, and drying the solid phase to obtain a primary modified powder;

[0006] (3) stirring and mixing the primary modified powder, furan-2,5-dione and chlorobenzene in an ultrasonic environment in a reactor for more than 10 minutes, sealing the reactor, filling it with nitrogen for protection, and then heating it to 125-140° C. for more than 2 hours, cooling it to room temperature, but adding sodium acetate and acetic anhydride in a nitrogen atmosphere, heating it to 125-140° C. for more than 1 hour, cooling it to room temperature, opening the reactor, separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, and then washing it with deionized water for more than 3 times, and drying it to obtain a doped powder;

[0007] (4) Drying the polycarbonate pellets at 120° C. for more than 10 hours, then mixing the dried polycarbonate pellets with the doped powder in a mixer for more than 5 hours, introducing the mixture into a twin-screw extruder for melt blending, extruding granulation, and injection molding the mixture in an injection molding machine to obtain the high temperature resistant polycarbonate-based composite material.

[0008] Furthermore, in the step (1), the mixed volume ratio of the ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 8-10: 3-4: 100, wherein the mass percentage of the solute in the ammonia water is 25%; and the volume ratio of the added volume of the tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 8-10: 100.

[0009] Furthermore, in the step (2), in the ethanol solution of 3-aminopropyltriethoxysilane, the mass percentage of 3-aminopropyltriethoxysilane is 10% to 15%, and the solvent is ethanol; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone is 13% to 16%, and the solvent is N,N-dimethylformamide; the silica powder is immersed in the ethanol solution of 3-aminopropyltriethoxysilane, and then deionized water is added in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 3 to 5:100:10 to 20; the dried solid phase is immersed in the N,N-dimethylformamide solution of sulfonated polysulfone in a mass ratio of dried solid phase: N,N-dimethylformamide solution of sulfonated polysulfone = 1 to 3:50.

[0010] Furthermore, in the step (3), the mass ratio of the primary modified powder to furan-2,5-dione and chlorobenzene is primary modified powder: furan-2,5-dione: chlorobenzene = 1-2: 4-6: 80; the mass ratio of the added sodium acetate and acetic anhydride to the mass of the primary modified powder is sodium acetate: acetic anhydride: primary modified powder = 0.3-0.5: 12-16: 1-2.

[0011] Furthermore, in the step (4), the mass ratio of the polycarbonate pellets to the doping powder is polycarbonate pellets:doping powder=99:1 to 98:2.

[0012] Furthermore, in the step (4), the injection molding melt temperature is 260° C. and the injection molding pressure is 70 to 80 MPa.

[0013] The beneficial effects of the present invention are that the polycarbonate-based composite material prepared by the method of the present invention has high mechanical strength and heat resistance, and its tensile strength and initial thermal degradation temperature are both high, which can meet the occasions with high material stress requirements and heat resistance requirements. The present invention can significantly improve the strength and heat resistance of the polycarbonate-based material by adding the filler to the polycarbonate after modification. This may be due to the following reasons: the present invention first treats the surface of the silica powder by 3-aminopropyltriethoxysilane to form a large number of amino groups on the surface of the silica powder, and then treats the amino-modified powder by sulfonated polysulfone, which improves the bonding force between the silica powder and the polycarbonate matrix material on the one hand, and the high bond energy and large bond angle structure contained in the introduced polysulfone structure can also improve the thermal stability of the polycarbonate itself on the other hand. The remaining amino groups on the surface of the silica powder are then functionalized with maleimide to improve the dispersibility of the filler in the material, and at the same time, it can also promote the bonding of the filler and the polycarbonate, reduce the defects between the filler and the matrix, improve the density and the bonding force between the two, and improve the strength and heat resistance of the material macroscopically. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the embodiments.

[0015] Example 1

[0016] A method for preparing a high temperature resistant polycarbonate-based composite material, the preparation steps comprising:

[0017] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of the mixed solution to the mixed solution is ammonia water: ethanol: deionized water = 8:3:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 8:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0018] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane; in the ethanol solution of 3-aminopropyl triethoxysilane, the mass percentage of 3-aminopropyl triethoxysilane is 10%, and the solvent is ethanol; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone (sulfonation degree is 30%) is 13%, and the solvent is N,N-dimethylformamide; soaking the silica powder in the ethanol solution of 3-aminopropyl triethoxysilane, stirring and mixing for 20 minutes, then adding deionized water to the solution under stirring, soaking the silica powder in the 3-aminopropyl triethoxysilane solution, stirring and mixing for 20 minutes, and then adding deionized water to the solution under stirring, and soaking the silica powder in the 3-aminopropyl triethoxysilane solution. The ethanol solution of oxysilane is then added with deionized water in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 3:100:10; after the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, the solid phase is dried at 80°C for 2 hours, the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone, and the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone in a mass ratio of the dried solid phase: the N,N-dimethylformamide solution of the sulfonated polysulfone = 1:50; stirring is performed for 20 minutes, and then solid-liquid separation is performed, and the solid phase is dried at 90°C for 5 hours to obtain a primary modified powder;

[0019] (3) The first modified powder, furan-2,5-dione and chlorobenzene are stirred and mixed in a reactor under ultrasonic environment for 10 minutes, wherein the mass ratio of the first modified powder, furan-2,5-dione and chlorobenzene is first modified powder: furan-2,5-dione: chlorobenzene = 1:4:80; the reactor is sealed, filled with nitrogen for protection, and then heated to 130° C. for 2 hours, and sodium acetate and acetic anhydride are added in a nitrogen atmosphere after cooling to room temperature, wherein the mass ratio of the added sodium acetate and acetic anhydride to the first modified powder is sodium acetate: acetic anhydride: first modified powder = 0.3:12:1; the reactor is heated to 130° C. for 1 hour, cooled to room temperature, opened, solid-liquid separation is performed, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 80° C. for 2 hours to obtain a doped powder;

[0020] (4) The polycarbonate (PC-110) pellets are dried at 120°C for 10 hours, and then the dried polycarbonate pellets are mixed with the doped powder in a mixer for 5 hours, wherein the mass ratio of the polycarbonate pellets to the doped powder is polycarbonate pellets: doped powder = 99:1; the mixture is introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures are both set to 260°C. The mixture is extruded and granulated, and the mixture is injection molded in an injection molding machine to obtain the high-temperature resistant polycarbonate-based composite material; the injection molding melt temperature is 260°C, and the injection molding pressure is 70 MPa.

[0021] Example 2

[0022] A method for preparing a high temperature resistant polycarbonate-based composite material, the preparation steps comprising:

[0023] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 9:3:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 9:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0024] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane; in the ethanol solution of 3-aminopropyl triethoxysilane, the mass percentage of 3-aminopropyl triethoxysilane is 12%, and the solvent is ethanol; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone (sulfonation degree is 30%) is 14%, and the solvent is N,N-dimethylformamide; soaking the silica powder in the ethanol solution of 3-aminopropyl triethoxysilane, stirring and mixing for 20 minutes, then adding deionized water to the solution under stirring, soaking the silica powder in the 3-aminopropyl triethoxysilane solution, stirring and mixing for 20 minutes, and then adding deionized water to the solution under stirring, and soaking the silica powder in the 3-aminopropyl triethoxysilane solution. The ethanol solution of oxysilane is then added with deionized water in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 4:100:14; after the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, the solid phase is dried at 80°C for 2 hours, and the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone, and the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone in a mass ratio of the dried solid phase: the N,N-dimethylformamide solution of the sulfonated polysulfone = 2:50; stirring is performed for 20 minutes, and then solid-liquid separation is performed, and the solid phase is dried at 90°C for 5 hours to obtain a primary modified powder;

[0025] (3) stirring and mixing the primary modified powder, furan-2,5-dione and chlorobenzene in an ultrasonic environment in a reactor for 10 minutes, wherein the mass ratio of the primary modified powder, furan-2,5-dione and chlorobenzene is primary modified powder: furan-2,5-dione: chlorobenzene = 1:5:80; sealing the reactor, filling it with nitrogen for protection, and then heating it to 130° C. for 2 hours, cooling it to room temperature but adding sodium acetate and acetic anhydride in a nitrogen atmosphere, wherein the mass ratio of the added sodium acetate and acetic anhydride to the primary modified powder is sodium acetate: acetic anhydride: primary modified powder = 0.4:14:1; heating it to 130° C. for 1 hour, cooling it to room temperature, opening the reactor, separating the solid and liquid, washing the solid phase with ethanol 3 times, and then washing it with deionized water 3 times, and drying it at 80° C. for 2 hours to obtain a doped powder;

[0026] (4) The polycarbonate (PC-110) pellets are dried at 120°C for 10 hours, and then the dried polycarbonate pellets are mixed with the doped powder in a mixer for 5 hours, wherein the mass ratio of the polycarbonate pellets to the doped powder is polycarbonate pellets: doped powder = 99:1; the mixture is introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures are both set to 260°C. The mixture is extruded and granulated, and the mixture is injection molded in an injection molding machine to obtain the high-temperature resistant polycarbonate-based composite material; the injection molding melt temperature is 260°C, and the injection molding pressure is 70 MPa.

[0027] Example 3

[0028] A method for preparing a high temperature resistant polycarbonate-based composite material, the preparation steps comprising:

[0029] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 9:4:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 9:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0030] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane; in the ethanol solution of 3-aminopropyl triethoxysilane, the mass percentage of 3-aminopropyl triethoxysilane is 14%, and the solvent is ethanol; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone (sulfonation degree is 30%) is 15%, and the solvent is N,N-dimethylformamide; soaking the silica powder in the ethanol solution of 3-aminopropyl triethoxysilane, stirring and mixing for 20 minutes, then adding deionized water to the solution under stirring, soaking the silica powder in the 3-aminopropyl triethoxysilane solution, stirring and mixing for 20 minutes, and then adding deionized water to the solution under stirring, and soaking the silica powder in the 3-aminopropyl triethoxysilane solution. The ethanol solution of oxysilane is added, and then deionized water is added in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 4:100:18; after the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, the solid phase is dried at 80°C for 2 hours, and the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone. The mass ratio of the dried solid phase immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone is the dried solid phase: the N,N-dimethylformamide solution of the sulfonated polysulfone = 2:50; stirring is performed for 20 minutes, and then solid-liquid separation is performed, and the solid phase is dried at 90°C for 5 hours to obtain a primary modified powder;

[0031] (3) The first modified powder, furan-2,5-dione and chlorobenzene are stirred and mixed in a reactor under ultrasonic environment for 10 minutes, wherein the mass ratio of the first modified powder, furan-2,5-dione and chlorobenzene is first modified powder: furan-2,5-dione: chlorobenzene = 2:5:80; the reactor is sealed, filled with nitrogen for protection, and then heated to 130° C. for 2 hours, and sodium acetate and acetic anhydride are added in a nitrogen atmosphere after cooling to room temperature, wherein the mass ratio of the added sodium acetate and acetic anhydride to the first modified powder is sodium acetate: acetic anhydride: first modified powder = 0.4:14:2; the reactor is heated to 130° C. for 1 hour, cooled to room temperature, opened, solid-liquid separation is performed, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 80° C. for 2 hours to obtain a doped powder;

[0032] (4) The polycarbonate (PC-110) pellets are dried at 120°C for 10 hours, and then the dried polycarbonate pellets are mixed with the doped powder in a mixer for 5 hours, wherein the mass ratio of the polycarbonate pellets to the doped powder is polycarbonate pellets: doped powder = 98:2; the mixture is introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures are both set to 260°C. The mixture is extruded and granulated, and the mixture is injection molded in an injection molding machine to obtain the high temperature resistant polycarbonate-based composite material; the injection molding melt temperature is 260°C, and the injection molding pressure is 70 MPa.

[0033] Example 4

[0034] A method for preparing a high temperature resistant polycarbonate-based composite material, the preparation steps comprising:

[0035] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 10:4:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 10:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0036] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane; in the ethanol solution of 3-aminopropyl triethoxysilane, the mass percentage of 3-aminopropyl triethoxysilane is 15%, and the solvent is ethanol; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone (sulfonation degree is 30%) is 16%, and the solvent is N,N-dimethylformamide; soaking the silica powder in the ethanol solution of 3-aminopropyl triethoxysilane, stirring and mixing for 20 minutes, then adding deionized water to the solution under stirring, soaking the silica powder in the 3-aminopropyl triethoxysilane solution, stirring and mixing for 20 minutes, and then adding deionized water to the solution under stirring, and soaking the silica powder in the 3-aminopropyl triethoxysilane solution. The ethanol solution of oxysilane is then added with deionized water in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 5:100:20; after the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed, the solid phase is washed with ethanol for 3 times, the solid phase is dried at 80°C for 2 hours, the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone, and the dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone in a mass ratio of the dried solid phase: the N,N-dimethylformamide solution of the sulfonated polysulfone = 3:50; stirring is performed for 20 minutes, and then solid-liquid separation is performed, and the solid phase is dried at 90°C for 5 hours to obtain a primary modified powder;

[0037] (3) The first modified powder, furan-2,5-dione and chlorobenzene are stirred and mixed in a reactor under ultrasonic environment for 10 minutes, wherein the mass ratio of the first modified powder, furan-2,5-dione and chlorobenzene is first modified powder: furan-2,5-dione: chlorobenzene = 2:6:80; the reactor is sealed, filled with nitrogen for protection, and then heated to 130° C. for 2 hours, and sodium acetate and acetic anhydride are added in a nitrogen atmosphere after cooling to room temperature, and the mass ratio of the added sodium acetate and acetic anhydride to the first modified powder is sodium acetate: acetic anhydride: first modified powder = 0.5:16:2; the reactor is heated to 130° C. for 1 hour, cooled to room temperature, opened, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and then washed with deionized water 3 times, and dried at 80° C. for 2 hours to obtain a doped powder;

[0038] (4) The polycarbonate (PC-110) pellets are dried at 120°C for 10 hours, and then the dried polycarbonate pellets are mixed with the doped powder in a mixer for 5 hours, wherein the mass ratio of the polycarbonate pellets to the doped powder is polycarbonate pellets: doped powder = 98:2; the mixture is introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures are both set to 260°C. The mixture is extruded and granulated, and the mixture is injection molded in an injection molding machine to obtain the high temperature resistant polycarbonate-based composite material; the injection molding melt temperature is 260°C, and the injection molding pressure is 70 MPa.

[0039] Comparative Example 1

[0040] A method for preparing a polycarbonate-based composite material as a comparison, the preparation steps comprising:

[0041] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 9:4:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 9:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0042] (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane; in the ethanol solution of 3-aminopropyltriethoxysilane, the mass percentage of 3-aminopropyltriethoxysilane is 14%, and the solvent is ethanol; soaking the silica powder in the ethanol solution of 3-aminopropyltriethoxysilane, stirring and mixing for 20 minutes, and then adding deionized water to the solution under stirring, soaking the silica powder in the ethanol solution of 3-aminopropyltriethoxysilane, and then adding deionized water in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 4:100:18; after the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and the solid phase is dried at 80°C for 2 hours to obtain a primary modified powder of this comparative example;

[0043] (3) The first modified powder, furan-2,5-dione and chlorobenzene are stirred and mixed in a reactor under ultrasonic environment for 10 minutes, wherein the mass ratio of the first modified powder, furan-2,5-dione and chlorobenzene is first modified powder: furan-2,5-dione: chlorobenzene = 2:5:80; the reactor is sealed, filled with nitrogen for protection, and then heated to 130° C. for 2 hours, and sodium acetate and acetic anhydride are added in a nitrogen atmosphere after cooling to room temperature, wherein the mass ratio of the added sodium acetate and acetic anhydride to the first modified powder is sodium acetate: acetic anhydride: first modified powder = 0.4:14:2; the reactor is heated to 130° C. for 1 hour, cooled to room temperature, opened, solid-liquid separation is performed, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 80° C. for 2 hours to obtain a doped powder;

[0044] (4) The polycarbonate (PC-110) pellets were dried at 120°C for 10 h, and then the dried polycarbonate pellets were mixed with the doping powder in a mixer for 5 h, and the mass ratio of the polycarbonate pellets to the doping powder was polycarbonate pellets: doping powder = 98:2; the mixture was introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures were set to 260°C. The mixture was extruded and granulated, and the mixture was injection molded in an injection molding machine to obtain the polycarbonate-based composite material of this comparative example; the injection molding melt temperature was 260°C, and the injection molding pressure was 70 MPa.

[0045] Comparative Example 2

[0046] A method for preparing a polycarbonate-based composite material as a comparison, the preparation steps comprising:

[0047] (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, wherein the volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 9:4:100, wherein the mass percentage of the solute in the ammonia water is 25%; the mixed solution is heated to 60±5° C. in a water bath and then stirred, and tetraethyl orthosilicate is added to the mixed solution under stirring, wherein the volume ratio of the added tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 9:100; after the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for 3 h to precipitate a solid phase, and then the solid-liquid is separated and the solid phase is dried at 80° C. for 2 h to obtain silicon dioxide powder;

[0048] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane; in the ethanol solution of 3-aminopropyl triethoxysilane, the mass percentage of 3-aminopropyl triethoxysilane is 14%, and the solvent is ethanol; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone (sulfonation degree is 30%) is 15%, and the solvent is N,N-dimethylformamide; soaking the silica powder in the ethanol solution of 3-aminopropyl triethoxysilane, stirring and mixing for 20 minutes, then adding deionized water to the solution under stirring, and soaking the silica powder in the 3-aminopropyl triethoxysilane. The mass ratio of silica powder: 3-aminopropyltriethoxysilane ethanol solution: deionized water is 4:100:18. After the addition is completed, stirring is continued for 90 minutes, and then solid-liquid separation is performed. The solid phase is washed with ethanol for 3 times, and the solid phase is dried at 80°C for 2 hours. The dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone. The dried solid phase is immersed in the N,N-dimethylformamide solution of the sulfonated polysulfone. The mass ratio of the dried solid phase: the N,N-dimethylformamide solution of the sulfonated polysulfone is 2:50. Stir for 20 minutes, and then separate the solid and liquid. The solid phase is dried at 90°C for 5 hours to obtain the doped powder of this comparative example.

[0049] (3) The polycarbonate (PC-110) pellets were dried at 120°C for 10 h, and then the dried polycarbonate pellets were mixed with the doping powder in a mixer for 5 h, and the mixing mass ratio of the polycarbonate pellets to the doping powder was polycarbonate pellets: doping powder = 98:2; the mixture was introduced into a twin-screw extruder for melt blending, and the barrel and die temperatures were both set to 260°C. The mixture was extruded and granulated, and the mixture was injection molded in an injection molding machine to obtain the polycarbonate-based composite material of this comparative example; the injection molding melt temperature was 260°C, and the injection molding pressure was 70 MPa.

[0050] Example 5

[0051] The thermal degradation behavior of the polycarbonate-based composite material prepared by the methods described in the above embodiments and comparative examples was tested by a thermogravimetric analyzer. The test temperature was from room temperature to 600°C, and the heating rate was 10°C / min to obtain the initial thermal degradation temperature. The tensile strength of the polycarbonate-based composite material prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T 1040.1-2018, and the tensile speed was set to 250mm / min. Five samples were tested in each group, and the average value was taken as the tensile strength of the group. The results are shown in Table 1.

[0052] As shown in Table 1, the polycarbonate-based composite material prepared by the method of the present invention has high mechanical strength and heat resistance, and its tensile strength and initial thermal degradation temperature are both high, which can meet the requirements for material stress and heat resistance. By comparing Example 3 of the present application with Comparative Examples 1 and 2, it can be seen that the present invention can significantly improve the strength and heat resistance of polycarbonate-based materials by adding the filler to polycarbonate after modification. This may be due to: the present invention first treats the surface of silica powder with 3-aminopropyltriethoxysilane to form a large number of amino groups on the surface of silica powder, and then treats the aminated powder with sulfonated polysulfone, which improves the bonding force between silica powder and polycarbonate matrix material on the one hand, and on the other hand, the high bond energy and large bond angle structure contained in the introduced polysulfone structure can also improve the thermal stability of polycarbonate itself. The remaining amino groups on the surface of the silica powder are then functionalized with maleimide to improve the dispersion of the filler in the material. This can also promote the combination of the filler and polycarbonate, reduce defects between the filler and the matrix, increase the density and the bonding strength between the two, and improve the strength and heat resistance of the material on a macro scale.

[0053] Table 1

[0054] Experimental Group Tensile strength(MPa) Onset thermal degradation temperature (℃) Example 1 80.7 476.2 Example 2 81.4 477.9 Example 3 86.6 483.0 Example 4 86.1 482.5 Comparative Example 1 74.9 469.8 Comparative Example 2 71.5 455.6

[0055] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a high temperature resistant polycarbonate-based composite material, characterized in that: The preparation steps include: (1) Ammonia water, ethanol and deionized water are mixed to form a mixed solution, the mixed solution is heated to 60±5° C. in a water bath to keep the temperature, and then the mixed solution is stirred. Tetraethyl orthosilicate is added to the mixed solution under stirring. After the addition is completed, the mixture is stirred at a constant temperature of 60±5° C. for more than 3 hours to precipitate a solid phase, and then the solid-liquid separation is carried out, and the solid phase is dried to obtain silicon dioxide powder; (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane; preparing an N,N-dimethylformamide solution of sulfonated polysulfone; soaking the silica powder in the ethanol solution of 3-aminopropyltriethoxysilane, stirring and mixing for more than 20 minutes, then adding deionized water to the solution under stirring, continuing to stir for more than 90 minutes after the addition is completed, then separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, drying, soaking the dried solid phase in the N,N-dimethylformamide solution of sulfonated polysulfone, stirring for more than 20 minutes, then separating the solid and the liquid, and drying the solid phase to obtain a primary modified powder; (3) stirring and mixing the primary modified powder, furan-2,5-dione and chlorobenzene in an ultrasonic environment in a reactor for more than 10 minutes, sealing the reactor, filling it with nitrogen for protection, and then heating it to 125-140° C. for more than 2 hours, cooling it to room temperature, but adding sodium acetate and acetic anhydride in a nitrogen atmosphere, heating it to 125-140° C. for more than 1 hour, cooling it to room temperature, opening the reactor, separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, and then washing it with deionized water for more than 3 times, and drying it to obtain a doped powder; (4) Drying the polycarbonate pellets at 120° C. for more than 10 hours, then mixing the dried polycarbonate pellets with the doped powder in a mixer for more than 5 hours, introducing the mixture into a twin-screw extruder for melt blending, extruding granulation, and injection molding the mixture in an injection molding machine to obtain the high temperature resistant polycarbonate-based composite material.

2. The method for preparing a high temperature resistant polycarbonate-based composite material according to claim 1, characterized in that: In the step (1), the mixed volume ratio of ammonia water, ethanol and deionized water is ammonia water: ethanol: deionized water = 8-10: 3-4: 100, wherein the mass percentage of the solute in the ammonia water is 25%; the volume ratio of the added volume of tetraethyl orthosilicate to the mixed solution is tetraethyl orthosilicate: mixed solution = 8-10:

100.

3. The method for preparing a high temperature resistant polycarbonate-based composite material according to claim 1, characterized in that: In the step (2), in the ethanol solution of 3-aminopropyltriethoxysilane, the mass percentage of 3-aminopropyltriethoxysilane is 10% to 15%, and the solvent is ethanol; in the N,N-dimethylformamide solution of sulfonated polysulfone, the mass percentage of sulfonated polysulfone is 13% to 16%, and the solvent is N,N-dimethylformamide; the silica powder is immersed in the ethanol solution of 3-aminopropyltriethoxysilane, and then deionized water is added in a mass ratio of silica powder: ethanol solution of 3-aminopropyltriethoxysilane: deionized water = 3 to 5:100:10 to 20; the dried solid phase is immersed in the N,N-dimethylformamide solution of sulfonated polysulfone in a mass ratio of dried solid phase: N,N-dimethylformamide solution of sulfonated polysulfone = 1 to 3:

50.

4. The method for preparing a high temperature resistant polycarbonate-based composite material according to claim 1, characterized in that: In the step (3), the mass ratio of the primary modified powder to furan-2,5-dione and chlorobenzene is primary modified powder: furan-2,5-dione: chlorobenzene = 1-2: 4-6: 80; the mass ratio of the added sodium acetate and acetic anhydride to the mass of the primary modified powder is sodium acetate: acetic anhydride: primary modified powder = 0.3-0.5: 12-16: 1-2.

5. The method for preparing a high temperature resistant polycarbonate-based composite material according to claim 1, characterized in that: In the step (4), the mass ratio of the polycarbonate pellets to the doping powder is polycarbonate pellets:doping powder=99:1-98:

2.

6. The method for preparing a high temperature resistant polycarbonate-based composite material according to claim 1, characterized in that: In the step (4), the injection molding melt temperature is 260° C. and the injection molding pressure is 70 to 80 MPa.